Leadership’s long arm: The positive influence of digital leadership on managing technology-driven change over a strengthened service innovation capacity - Brunner, Timo J. J.; Schuster, Tobias; Lehmann, Claudia (Frontiers in Psychology, 2023)
In this qualitative study, we examine digital leadership (DL) capabilities and their positive influence on the management of technology-driven change by leveraging service innovations. The context of digital transformation (DT) has triggered a new leadership paradigm, among others referred to as digital leadership (DL). However, despite its practical relevance, leadership research has yet paid little attention to conceptualise DL as an approach to digitally transform organisations. Drawing on mid- and top-level mangers’ experiences with service innovation projects, and based on Grounded Theory, we develop a taxonomy of DL-related capabilities and a conceptual framework which exemplifies their influences on dynamic service innovation capabilities (DSICs). DSICs build on the dynamic capabilities view (DCV) and represent the “organisational muscle” to repeatedly deliver service innovations indicating an effective management of technology-driven change. Taxonomy results show that aggregated dimensions in terms of a digital leader’s personal, social, and organisational capital serve as underpinnings (DL-related capabilities) to drive strategic change in DT contexts. The conceptual framework further reveals that especially the personal and organisational capital of a digital leader owns several strong and moderate influences on DSICs which demonstrates DL’s “long arm” on the management of technology-driven change. Our findings contribute to leadership research by advancing the conceptualisation of DL and by adding a novel micro-foundational perspective towards the DCV discourse. As organisations struggle to realise the full benefits of DT initiatives, our results also provide a valuable contribution for practitioners by supporting them to strategically prepare for the human-related challenges of DT.